Optimization of the electrostatic structure of the ion microprobe - I. G. Ignat'ev; V. I. Miroshnychenko; O. G. Ponomarev; V. Yu. Storizhko (Ядерна фізика та енергетика)
The paper presents optimization data obtained for an immersion probe-forming system of the ion microprobe to be used in 3 MeV H+ ion accelerator generating 0,4 μm beam spot for normalized acceptance of 7 μm2 · mrad2 · MeV. To achieve higher microprobe resolution it is intended to place an electrostatic lens between the collimators and the accelerating tube.